Nursing Entrepreneurship Opportunities Through Product Innovation Jellowry: Low-Calorie Jelly With Tamarindus Indica Leaf Extract As A Healthy Food Variation For Reducing Weight And Calories For Obesity Patients - Ahdiah, Danies Laelatul; Puspita, Asih Purwandari Wahyoe; Kamalia, Annisa; Amelia, Ayu; Adha, Sakinah Nurlaela; Maulida, Nova Masripah (Indonesian Journal of Community Development, 2023)
Porang flour is a product produced from the tubers of the porang plant (Amorphophallus oncophyllus). This porang plant grows in various tropical and subtropical regions of the world, especially in Southeast Asia. Porang flour has long been used in various food, industrial and health applications, because it has a variety of important functions. The aim of making jellowry to create an innovative Local Kojelly product is to overcome obesity through a variety of healthy foods to reduce weight and calories and support the Indonesian Ministry of Health program GERMAS (healthy living community movement) as one way to overcome obesity. Forms of entrepreneurial activity include the preparation, implementation, packaging and evaluation stages of Jellowry products. The target users of the product are the target users of Jellowry's innovative products are the general public aged 1-60 years (including the elderly, children over 1 year old, pregnant women breastfeeding mothers) and especially obesity and diabetes sufferers. The results of the activity show that the use of Jellowry products has a positive impact on society.